Analgesic Effectiveness and Dorsal Root Ganglia Protein Modulation of a Peripheral Adenosine Monophosphate Kinase Alpha Activator (O304) Following Lumbar Disk Puncture in the Mouse. (6th October 2022) - Das, Vaskar; Basovich, Michael B.; Kroin, Jeffrey S.; Buvanendran, Asokumar; McCarthy, Robert J.
Abstract : BACKGROUND: Disk herniation is a primary cause of radicular back pain. The purpose of this study was to evaluate the antiallodynic effective dose in 50% of the sample (ED50 ) and dorsal root ganglion (DRG) protein modulation of a peripheral direct adenosine monophosphate kinase alpha (AMPKα) activator (O304) in a murine model of lumbar disk puncture. METHODS: Male (n = 28) and female (n = 28) mice (C57BL6/J) were assessed for hind paw withdrawal threshold (PWT) and burrowing. Abdominal surgery was performed on all mice, and 48 received a lumbar disk puncture (27-G needle), with 8 serving as nondisk puncture controls. Assessments were repeated at day 7, and mice were then randomized into 5 groups of equal numbers of males and females: O304 at 100 mg/kg (n = 10), 150 mg/kg (n = 10), 200 mg/kg (n = 10), and 250 mg/kg (n = 10) or drug vehicle (n = 8). Starting on day 7, mice received daily gavages of O304 or vehicle for 7 days. On days 14 and 21 PWT and on day 14 burrowing were assessed. The area under the PWT by time curve (AUC) from day 7 to 21 was determined by trapezoidal integration. DRG protein modulation was evaluated in male (n = 10) and female (n = 10) mice (C57BL6/J). Following disk puncture, mice were randomized to receive O304 200 mg/kg or vehicle for 7 days starting on day 7. On day 14, mice were euthanized; the DRG harvested and immunoblot performed for mammalian target of rapamycin (mTOR), transient receptor potential ankyrin 1 (TRPA1), phosphorylated adenosine monophosphate kinase (p-AMPK), phosphorylated extracellular signal-regulated kinase (p-ERK), phosphorylated eukaryotic translation initiation factor 2 subunit 1 (p-EIF2S1), phosphorylated eukaryotic translation initiation factor 4e (p-EIF4E), and glyceraldehyde 3-phosphate dehydrogenase (GADPH). RESULTS: Disk puncture decreased PWT greater in female mice compared with male mice and decreased burrowing at 7 days. PWTs were increased with increasing doses of O304 from 150 to 250 mg/g on day 14 and sustained through day 21. The ED50 (95% confidence interval [CI]) for reducing mechanical allodynia was 140 (118–164) mg/kg. Burrowing was not increased at day 14 compared to day 7 by O304 administration. Compared to vehicle-treated animals, O304 increased (95% CI) the p-AMPK/GADPH ratio, difference 0.27 (0.08–0.45; P = . 004) and decreased (95% CI) the ratios of p-TRPA1, p-ERK1/2, pEIF4E, and p-EIF2S1 to GADPH by −0.49 (−0.61 to −0.37; P < . 001), −0.53 (−0.76 to −0.29; P < . 001), −0.27 (−0.42 to 0.11; P = . 001), and −0.21 (−0.32 to −0.08; P = . 003) in the DRG, respectively. CONCLUSIONS: The direct peripheral AMPK activator O304 reduced allodynia in a dose-dependent manner, and immunoblot studies of the DRG showed that O304 increased p-AMPK and decreased TRPA1, p-ERK1/2, as well as translation factors involved in neuroplasticity. Our findings confirm the role of peripheral AMPKα activation in modulating nociceptive pain.